The Alteration of Emotion Regulation Precedes the Deficits in Interval Timing in the BACHD Rat Model for Huntington Disease - Garces, Daniel; El Massioui, Nicole; Lamirault, Charlotte; Riess, Olaf; Nguyen, Huu P.; Brown, Bruce L.; Doyère, Valérie (Frontiers in Integrative Neuroscience, 2018)
Huntington disease (HD) is an autosomal dominantly inherited, progressive neurodegenerative disorder which is accompanied by executive dysfunctions and emotional alteration. The aim of the present study was to assess the impact of emotion/stress on on-going highly demanding cognitive tasks, i.e. temporal processing, as a function of age in BACHD rats (a "full length" model of HD). Middle-aged (4-6 months) and old (10-12 months) rats were first trained on a 2 vs 8-s temporal discrimination task, and then exposed to a series of bisection tests under normal and stressful (10 mild unpredictable foot-shocks) conditions. The animals were then trained on a peak interval task, in which reinforced fixed-interval (FI) 30-s trials were randomly intermixed with non-reinforced probe trials. After training, the effect of stress upon time perception was again assessed. Sensitivity to foot-shocks was also assessed independently. The results show effects of both age and genotype, with largely greater effects in old BACHD animals. The older BACHD animals had impaired learning in both tasks, but reached equivalent levels of performance as WT animals at the end of training in the temporal discrimination task, while remaining impaired in the peak interval task. Whereas sensitivity to foot-shock did not differ between BACHD and WT rats, delivery of foot-shocks during the test sessions had a disruptive impact on temporal behavior in WT animals, an effect which increased with age. In contrast, BACHD rats, independent of age, did not show any significant disruption under stress. In conclusion, BACHD rats showed a disruption in temporal learning in late symptomatic animals. Age-related modification in stress-induced impairment of temporal control of behavior was also observed, an effect which was greatly reduced in BACHD animals, thus confirming previous results suggesting reduced emotional reactivity in HD animals. The results suggest a staggered onset in cognitive and emotional alterations in HD, with emotional alteration being the earliest, possibly related to different time courses of degeneration in cortico-striatal and amygdala circuits.